Analysis of the effect of economic growth toward the center of the overflow area and hinterlend in determining nodal centre of new growth on the area of Mamminasata in South Sulawesi - Zainuddin Rahman (Indonesia Prime, 2017)
This research conducted in Mamminasata District, South Sulawesi Province. This study examines the Economic Effects of the overflow